Understanding ChatGPT: A Worldview Study - Suryo, Bramantyo; Muttaqin, Muhammad Azhar; Mulia Insani, Iftitah Afiat; Affandi, Muchammad Taufiq (TSAQAFAH, 2024)
This study compares the Islamic worldview, which emphasizes religious authority and intuition as sources of knowledge, and the contemporary worldview, which focuses on rationalism and empiricism. From the Islamic perspective, the tradition of khabar shadiq, which is based on revelation and religious authority, serves as the foundation of knowledge, differing from the Western view that relies more on the scientific method and various data sources, including big data. Modern technology, such as ChatGPT, which utilizes big data, raises ethical and epistemological questions in the Islamization of science. ChatGPT itself faces limitations in its knowledge, while big data often encounters issues of inaccuracy and bias. Therefore, serious consideration is needed regarding ethics in developing and using technology like ChatGPT and its alignment with Islamic values in modern technology. This study highlights the importance of considering epistemological and ethical issues in modern technology to ensure a positive contribution to the advancement of Islamic civilization while maintaining the integrity of values from the Islamic worldview perspective.